Scorpionism due to Tityus neoespartanus (Scorpiones, Buthidae) in Margarita Island, northeastern Venezuela Escorpionismo por Tityus neoespartanus (Scorpiones, Buthidae) na Ilha de Margarita, Nordeste da Venezuela - Leonardo De Sousa; Jenny Boadas; Demetrio Kiriakos; Adolfo Borges; Jesús Boadas; Jenny Marcano; Iván Turkali; Miguel De Los Ríos (Revista da Sociedade Brasileira de Medicina Tropical, 2007)
The first two cases of scorpion envenoming caused by Tityus neoespartanus (Buthidae) are described. The accidents took place within human environments (one inside a home and the other inside a school), in the village of La Sierra, Margarita Island, State of Nueva Esparta, northeastern Venezuela. Both cases were moderately severe and developed pancreatic involvement and electrocardiographic abnormalities. This report allows inclusion of Margarita Island among the endemic areas of scorpionism in Venezuela. Descrevem se os dois primeiros casos de escorpionismo por Tityus neoespartanus (Scorpiones, Buthidae). Os acidentes ocorreram no ambiente antrópico (um no domicilio e outro na escola) na aldeia de La Sierra, Ilha de Margarita, Estado de Nueva Esparta, nordeste da Venezuela. Os dois acidentes, moderadamente graves, cursaram com acometimento pancreático e alterações eletrocardiografias. Este reporte permite incluir à Ilha de Margarita entre as áreas endêmicas de escorpionismo na Venezuela.